2010
DOI: 10.1152/ajpgi.00262.2009
|View full text |Cite
|
Sign up to set email alerts
|

Liver apoptosis is age dependent and is reduced by activation of peroxisome proliferator-activated receptor-γ in hemorrhagic shock

Abstract: Zingarelli B, Chima R, O'Connor M, Piraino G, Denenberg A, Hake PW. Liver apoptosis is age dependent and is reduced by activation of peroxisome proliferator-activated receptor-␥ in hemorrhagic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
2
4
0
1
Order By: Relevance
“…We have previously demonstrated that PPARγ plays an important protective role in hemorrhagic shock, since PPARγ ligands are able to reduce organ injury and improve cardiovascular function in male rodents [4244]. In the present study, we found that PPARγ activity was upregulated in an age-dependent, but not gender-dependent manner after hemorrhagic shock.…”
Section: Discussionsupporting
confidence: 63%
“…We have previously demonstrated that PPARγ plays an important protective role in hemorrhagic shock, since PPARγ ligands are able to reduce organ injury and improve cardiovascular function in male rodents [4244]. In the present study, we found that PPARγ activity was upregulated in an age-dependent, but not gender-dependent manner after hemorrhagic shock.…”
Section: Discussionsupporting
confidence: 63%
“…A non-significant trend towards higher mitochondrial pro- to anti-apoptotic ratio (BAX: Bcl-2) in old age was also observed however we did not find increased cytochrome C, AIF release or caspase-9 activation, which are intermediates involved in signaling downstream apoptosis. Consistent with other research (Molpeceres et al, 2007; Zhang et al, 2002; Zingarelli et al, 2010) we found increased protein levels of apoptosis markers activated caspase-3, -6 and -7 in old age and a trend towards an increase in apoptotic DNA fragmentation that may be activated by mechanisms of apoptosis (Elmore, 2007) other than the intrinsic death pathway. These results suggest that in old Fischer 344 rats complex changes occur in the intrinsic cell death pathway and apoptosis that include altered mitochondrial apoptotic protein levels, subcellular localization, signaling and increased overall apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Pgc-1α acts with transcription factors such as Ppar-γ, retinoid receptor (RXR)-α and nuclear respiratory factor-1 (Nrf-1). It has been shown previously that Ppar expression after T-H decreases, and its augmented expression reduces liver apoptosis following T-H (46). Upon events such as oxidative or cold stress, expression of Pgc-1α is upregulated by transcriptional activities and downstream target genes are activated (47).…”
Section: Discussionmentioning
confidence: 95%